(untitled) (Culturas Científicas, 2026)
In this article, we address the question of whether Bohmian mechanics provides a scientific explanation of phenomena and whether its explanatory power depends on the chosen interpretation of the theory. More particularly, we focus on the debate concerning the nature of the wave function, considering three interpretations: (i) that it represents a physical field; (ii) that it is an aspect of the particles’ law of motion; and (iii) that it represents a dispositional property of the particles. In a recent paper, Esfeld et al. (2014) consider these three alternatives, arguing that the dispositional interpretation is superior in explanatory terms. For our analysis, we use Díez’s (2014), according to which scientific explanations are instances of ampliative and specialized nomological embeddings. We conclude that Bohmian mechanics is explanatory and that its capacity to provide an adequate scientific explanation of phenomena does not depend on the interpretation of the theory, clarifying how alleged differences in explanatory power, such as those invoked by Esfeld et al. (2014), should be understood.